Revealing the oxidation growth mechanism and crack evolution law of novel Si–HfO2/Yb2Si2O7/Yb2SiO5 environmental barrier coatings during thermal cycling - Ruixiang Liu; Wenping Liang; Qiang Miao; Hui Zhao; Xiaofeng Zhang; Meng Zhang; Rongxue Yan; Brindha Ramasubramanian; Seeram Ramakrishna (Journal of Advanced Ceramics)
The development of Si–HfO2/Yb2Si2O7/Yb2SiO5 environmental barrier coatings (EBCs) aims to improve the operational temperature and longevity of ceramic matrix composites (CMCs) in turbine environments. Nevertheless, several critical questions remain unanswered, including the oxidation mechanism of Si–HfO2 bond coating, the compatibility of its mixed thermally grown oxide (m-TGO) with adjacent layers during thermal cycling, and the evolution pattern of vertical mud-cracks that impact the overall performance in service. Using plasma spraying physical vapor deposition (PS-PVD), we fabricated these EBCs on a CMC substrate, and thermal cycling tests at 1400, 1450, and 1500 °C revealed that their durability reached 200 h. m-TGO growth followed a parabolic model, with the oxygen diffusion activation energy being 133.69 kJ/mol between 1400 and 1450 °C and 101.47 kJ/mol from 1450 to 1500 °C, emphasizing that the transport of molecular oxygen is key to controlling the oxidation of m-TGO in this EBC system. Although residual stresses and stored elastic strain energy build up between m-TGO and adjacent layers, especially around the cristobalite phase transition temperature, causing interlaminar crack formation in later thermal cycles, the stored elastic strain energy remains lower than that of the silicon oxide–thermally grown oxide (SiO2–TGO) formed in Si bond coating system. In addition to [110] dislocations, (001) twinning and interaction zones between twinning and dislocations were discovered for the first time, driving the bifurcation of mud cracks. Notably, controlling the mud-crack density is vital for protection of Yb2SiO5 layer, as bifurcated mud-crack tips may converge with adjacent mud-cracks.